Quality of River Water in the District Area of Middle of Java - Nurbaya, Fiqi; Oktavia, Yohana Fide; Johar, Syefira Ayodia (Media Karya Kesehatan, 2024)
The decline in river air quality is characterized by a decline in air quality parameters, namely physical, chemical and microbiological parameters. Preliminary studies revealed that the physical and chemical parameters of TSS, BOD were respectively 52 mg/L, 57 mg/L, the test results were not in accordance with Government Regulation no. 22 of 2021 concerning Implementation of Environmental Protection and Management. The aim of this research is to determine the quality of river water based on physical and chemical parameters, namely Total Suspended Solid (TSS), Total Dissolved Solid (TDS), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Dissolved Oxygen (DO), water potential hydrogen (pH) in Karanganyar Regency. This research method is quantitative descriptive using laboratory tests, with samples from 6 rivers in each sub-watershed. The sampling technique uses Integrated Sampling by carrying out laboratory testing. Data analysis uses air quality measurements using the pollutant index method. The parameters tested are physical parameters, namely TSS, TDS and chemical parameters, namely COD, BOD, DO and pH. The research results show that the TSS parameters exceed the quality standards, TDS corresponds to the quality standards, COD exceeds the quality standards, BOD exceeds the quality standards, DO corresponds to the quality standards, pH does not comply with the quality standards. The conclusions in this research are that the Jlamprang River sub-watershed of Kudus is 1.99 (lightly polluted), the Bagor River is sub-watershed of Jlantah 2.31 (lightly polluted), the Gembong River is sub-watershed of Samin 6.94 (moderately polluted), the Kumpul River is sub-watershed of Mungkung 2 .74 (lightly polluted), Kendat River, Kenatan sub-watershed, 2.67 (lightly polluted), Pepe River, Pepe sub-watershed, 2.14 (lightly polluted). The suggestion for the Karanganyar District Government is to monitor river water quality regularly Keywords: Chemical Oxygen Demand, Biological Oxygen Demand, Dissolved Oxygen.